2010
DOI: 10.3168/jds.2010-3409
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and peptidomic study of proteolysis in quarter milk after infusion with lipoteichoic acid from Staphylococcus aureus

Abstract: Mastitic milk is associated with increased bovine protease activity, such as that from plasmin and somatic cell enzymes, which cause proteolysis of the caseins and may reduce cheese yield and quality. The aim of this work was to characterize the peptide profile resulting from proteolysis in a model mastitis system and to identify the proteases responsible. One quarter of each of 2 cows (A and B) was infused with lipoteichoic acid from Staphylococcus aureus. The somatic cell counts of the infused quarters reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 60 publications
7
55
0
Order By: Relevance
“…There are only a very small number of studies in which peptide analysis has been performed on bovine milk samples during mastitis [15,25]. Both studies employed the same method, RP-HPLC, in separating the peptides, while further protein characterization was performed by MALDI-TOF/MS/ MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only a very small number of studies in which peptide analysis has been performed on bovine milk samples during mastitis [15,25]. Both studies employed the same method, RP-HPLC, in separating the peptides, while further protein characterization was performed by MALDI-TOF/MS/ MS.…”
Section: Discussionmentioning
confidence: 99%
“…Following induction of mastitis by infusion of lipoteichoic acid (LTA), the toxin of S. aureus, Larsen et al [15] identified, by 2-D gel electrophoresis, hydrolysis of β-and α S1 -caseins 6 h after infusion with the toxin. Examination of the peptides at this and later time points, using reversedphase HPLC and MALDI-TOF MS/MS, detected increases in the milk peptidome with several different peptides being characterized and found to originate from α S1 -and β-caseins.…”
Section: Introductionmentioning
confidence: 99%
“…2-DE was performed as described by Larsen et al (2010). Stained gels were then scanned using a calibrated GS-800 densitometer (Bio-Rad, Hercules, CA, USA)…”
Section: One-and Two-dimensional Gel Electrophoresismentioning
confidence: 99%
“…Plasmin is primarily responsible for the observed proteolysis in milk with a low SCC, whereas cathepsins and elastase are implicated in proteolysis of milk with an elevated cell count (Wedholm et al, 2008). Increases in milk SCC (from 55 3 10 3 to 1382 3 10 3 cells/ml) have been correlated with increased plasmin, cathepsin D and cysteine protease activity (Somers et al, 2003), and with concomitant increases in proteolysis in milk, leading to the formation of a lower molecular weight casein fraction (Larsen et al, 2010). In our study, fragments of b-casein and a s1 -casein likely originated from increased caseinolysis in the milk of cows that received post-ruminal infusion of LNA at 400 g/day.…”
Section: Discussionmentioning
confidence: 99%